FACTOR ANALYSIS OF THE CO2 EMISSIONS IN THE UNITED STATES WITH IMPLICATIONS FOR THE ENVIRONMENTAL POLICY - Dias, Olen; Vaninsky, Alexander (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This paper applies the Generalized Divisia Index to decompose the CO2 emissions into eight components and uses the Factor Analysis to determine their clusters - the combinations of related components that play the leading role. Economic analysis of these clusters allows for the determination of the main drivers of the CO2 emissions. As a case study, we used the data of the United States from 1950 through 2040 separated into three periods: 1950 - 1980; 1981 - 2012, and 2013 - 2040, each characterized by a specific type of socioeconomic development: industrial, post-industrial, and information, respectively. Data for the last period are projections. As a result, we got an insight into the typology of the CO2 emissions and obtained recommendations on environmental policy aimed at their mitigation.